2016
DOI: 10.4103/2229-516x.179027
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus-associated cancers: A growing global problem

Abstract: Human papillomavirus (HPV) infection is linked with several cancers such as cancer cervix, vagina, vulva, head and neck, anal, and penile carcinomas. Although there is a proven association of HPV with these cancers, questions regarding HPV testing, vaccination, and treatment of HPV-related cancers continue to remain unanswered. The present article provides an overview of the HPV-associated cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(69 citation statements)
references
References 50 publications
0
64
0
5
Order By: Relevance
“…In addition, other viruses with oncogenic potential such as EBV and MCPV that have been detected in the nasopharyngeal tract, tonsils, salivary glands, and lungs may play an important role ( Baez et al, 2015 ; Pezzuto et al, 2015 ; Gupta et al, 2016 ). At present, there are insufficient reports describing the epidemiology of viral coinfections in tumors of the larynx, so studies in this regard could contribute to clarify their association with the carcinogenic progression and to facilitate preventive strategies ( Bansal, Singh & Rai, 2016 ). A total of 195 specimens of laryngeal tumor tissue were included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other viruses with oncogenic potential such as EBV and MCPV that have been detected in the nasopharyngeal tract, tonsils, salivary glands, and lungs may play an important role ( Baez et al, 2015 ; Pezzuto et al, 2015 ; Gupta et al, 2016 ). At present, there are insufficient reports describing the epidemiology of viral coinfections in tumors of the larynx, so studies in this regard could contribute to clarify their association with the carcinogenic progression and to facilitate preventive strategies ( Bansal, Singh & Rai, 2016 ). A total of 195 specimens of laryngeal tumor tissue were included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…More than 200 HPV types have been identified (Ghedira et al, 2016) and some had been confirmed to be associated with certain diseases, mainly cancers. Replicated evidence support that HPV infection causes cervical cancer in virtually 100% of cases and it is associated with the development of an important percentage of penile, vaginal, anal, vulvar, and oropharyngeal cancers and pre-cancers (Bansal, Singh & Rai, 2016). Epidemiological research has reported that 5.2% of all cancers worldwide can be attributed to HPV infection (Steben & Duarte-Franco, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…CANCERPLEX includes probes that correspond to HPV and EBV biomarkers. Infection with these agents confers an increased risk of developing several different types of cancer, including head and neck and cervical cancer [ 25 , 26 ] and have implications on tumor classification, prognosis and treatment strategies [ 27 , 28 ]. The proficiency of the assay to detect these viruses was evaluated by testing a set of previously characterized virus-positive and -negative human DNAs, including clinical FFPE tumors, HeLa cells and two DNA samples derived from EBV-transformed cell lines.…”
Section: Resultsmentioning
confidence: 99%